INFORACADEMIA: INFORMATION OFFER FOR THE CREATION OF LEARNING RESOURCES IN THE CUBAN UNIVERSITY CONTEXT: oferta de información para la creación de recursos de aprendizaje en el contexto universitario cubano - Paz Enrique, Luis Ernesto; Hernández Alfonso, Eduardo Alejandro (Informação em Pauta, 2024)
The design of information offers for the creation of learning resources enhances the acquisition of skills by university professors. The Editorial Universitaria Félix Varela stands out for the number of texts they edit and their wide distribution nationwide. At the request of the publisher, it is necessary to create information offers that facilitate the creation of learning resources by university professors. In addition to the above, there is a low scientific production of scientific books for teaching. The objective of the study was to prepare an information offer that facilitates the creation of learning resources in the Cuban university context. The study classifies as mixed, predominantly qualitative. To obtain results, methods were used at the theoretical and empirical levels, mainly the survey. The characteristics of the potential users for the design of the information offer InforAcademia were identified. The offer has three information products: a manual, a tutorial and a video tutorial.